TFEB signaling attenuates NLRP3‐driven inflammatory responses in severe asthma. Issue 7 (25th January 2022) - Theofani, Efthymia; Semitekolou, Maria; Samitas, Konstantinos; Mais, Annie; Galani, Ioanna E.; Triantafyllia, Vasiliki; Lama, Joanna; Morianos, Ioannis; Stavropoulos, Athanasios; Jeong, Se‐Jin; Andreakos, Evangelos; Razani, Babak; et al.
Abstract: Background: NLRP3‐driven inflammatory responses by circulating and lung‐resident monocytes are critical drivers of asthma pathogenesis. Autophagy restrains NLRP3‐induced monocyte activation in asthma models. Yet, the effects of autophagy and its master regulator, transcription factor EB (TFEB), on monocyte responses in human asthma remain unexplored. Here, we investigated whether activation of autophagy and TFEB signaling suppress inflammatory monocyte responses in asthmatic individuals. Methods: Peripheral blood CD14 + monocytes from asthmatic patients ( n = 83) and healthy controls ( n = 46) were stimulated with LPS/ATP to induce NLRP3 activation with or without the autophagy inducer, rapamycin. ASC specks, caspase‐1 activation, IL‐1β and IL‐18 levels, mitochondrial function, ROS release, and mTORC1 signaling were examined. Autophagy was evaluated by LC3 puncta formation, p62/SQSTM1 degradation and TFEB activation. In a severe asthma (SA) model, we investigated the role of NLRP3 signaling using Nlrp3 −/− mice and/or MCC950 administration, and the effects of TFEB activation using myeloid‐specific TFEB‐overexpressing mice or administration of the TFEB activator, trehalose. Results: We observed increased NLRP3 inflammasome activation, concomitant with impaired autophagy in circulating monocytes that correlated with asthma severity. SA patients also exhibited mitochondrial dysfunction and ROS accumulation. Autophagy failed to inhibit NLRP3‐driven monocyte responses, due to defective TFEB activation and excessive mTORC1 signaling. NLRP3 blockade restrained inflammatory cytokine release and linked airway disease. TFEB activation restored impaired autophagy, attenuated NLRP3‐driven pulmonary inflammation, and ameliorated SA phenotype. Conclusions: Our studies uncover a crucial role for TFEB‐mediated reprogramming of monocyte inflammatory responses, raising the prospect that this pathway can be therapeutically harnessed for the management of SA. Abstract : We investigate whether activation of autophagy and TFEB signaling suppress inflammatory monocyte responses in asthmatic individuals. Our studies reveal a dysregulation of NLRP3 inflammasome and autophagy responses in monocytes from asthmatics that correlate with disease severity. In vivo activation of the autophagy inducer, TFEB, through trehalose administration or myeloid cell‐specific TFEB overexpression, restrains pulmonary inflammation and attenuates asthma features, uncovering TFEB as a novel therapeutic target.Abbreviations: c‐di‐GMP/HDM, cyclic di‐guanosine monophosphate/house dust mite; Dex, dexamethasone; MCC950, NLRP3 inhibitor; mTORC1, mammalian target of rapamycin complex 1; NLRP3, NLR family, pyrin domain‐containing 3; TFEB, transcription factor EB; Tg, transgenic